A New (Alternative) Model of Heart Lesion in Rat: A Step to Cardiomyoblast Grafting for Cardiac Tissue Repair - Sébastien Quéron; Véry Coulic; Constantin Stefanidis; Paul Delrée; Carine de Prez; Esmail Najar Saligheh; Pierre Bergmann (Highlights on Medicine and Medical Research Vol. 4, 2021)
An experiment on 57 rats was performed in order to elaborate an alternative model of cardiac lesion. The antero-apical area of the heart (i.e. a part of right, septum and left ventricles) was cauterized with a «Cautery high temperature fine tip» (Bovie Medical Corporation-USA) to create an injury of controllable, precise and reproducible dimensions (8x8 mm2 surface, 1 mm depth). To evaluate functional and morphological characteristics of the lesion, electrocardiography, pulse oximetry, echocardiography and optic microscopy were performed at different times (from day 0 to 230) after the operation. After technical adjustment a 100% survival of the last 12 operated animals was obtained. A sub epicardial “infarction” was documented (ST-modifications on the ECG in 2 leads, significant decrease of the ejection fraction (37.4% at day 10+/-2 and 27.3% at day 30+/-5), necrotic alterations and fibrosis of the lesion area in the myocardium). The survival and the evolution of the injury suggest that the proposed model could be used for studies concerning cardiac tissue repair.